איך לפשט (x + 2) / (4x ^ 2 - 14x + 6) - (x + 4) / (x ^ 2 + x -12)?

איך לפשט (x + 2) / (4x ^ 2 - 14x + 6) - (x + 4) / (x ^ 2 + x -12)?
Anonim

תשובה:

# X 2x = 16x + 16 / x-3 (4x-2) (x + 4) #

הסבר:

פקטור הראשון.

# (x + 2) / (4x ^ 2-14x + 6) - (x + 4) / (x ^ 2 + x-12) #

= # (x + 2) / (x-3) (4x-2)) (x + 4) / (x + 4) (x-3)

עבור לשברים דומים על ידי מקבל #LCD = (x -3) (4x-2) (x-3) #

= - (x + 2) (x + 2) (x + 4) / (x-3) (4x-2) (x + 4)) (4x-2) (x + 4)) #

= # (x + 2) (x + 4) - (x + 4) (4x-2) / (x + 3) (4x-2) (x + 4)

השתמש רכוש חלוקה של כפל.

# (x = 2 + 4x + 2x + 8) - (4x ^ 2xx + 16x-8) / x-3 (4x-2) (x + 4)

שלב כמו מונחים.

# = -3x ^ 2-8x + 16 / x-3 (4x-2) (x + 4) #